As raízes da poesia infantil de Zalina Rolim em livro das crianças - Oliveira, Valnikson Viana de (2017)
The present dissertation aims to investigate if there was, in fact, beyond the manifestation of the pedagogical ideology disseminated during the implantation of the republican regime in Brazil, an aesthetic concern related to the seduction and delight of the infantile recipient within the poetic collection Livro das crianças (1897), by the writer and educator Zalina Rolim. This compendium constitutes a notable example of the creation directed to a reader in formation within the cultural system of the late nineteenth century, being adopted as a reading book by public schools and integrating the process of renewal in the teaching propagated in that period. The research, of a bibliographic and documentary nature, turned more precisely to the discussion and analysis of the most representative compositions of the educational orientation linked to the work and those that demonstrate certain technical components aimed to an intentionality not so utilitarian with its target audience, also evoking the study of the significant illustrations present in the compendium. For this purpose, we report on the social, political and cultural circumstances that have involved the origin of children's literature, as well as evoking their emergence in the national context. In addition, we explored the author's biography looking for a better understanding of the motivations and influences of her production, which we seek to launch a new critical look at the academic scene. Throughout the study, we realize that many of Rolim's children's verses do not manifest an evident didactic purpose, incorporating seductive and amusing artifices of the boys and girls of the last years the 19th century. Even not being able to break with the artistic limitations from its time, the work presents an interesting contrast in comparison with other publications linked to schooling process and contemporaneous to its launching.